CRB modification to retromandibular approach for management of subcondylar fractures. (International Journal of Medical and Surgical Sciences, 2019)
The aim of this study was to evaluate the efficacy of CRB modification of retromandibular approach to gain surgical access for open reduction and internal fixation of mandibular subcondylar fractures. A total number of 264 sustained extra-capsular subcondylar fractures from 230 patients were selected for the study over the period of 5 years. Evaluation of intraoperative accessibility, postoperative facial nerve function, postoperative complications and scar was carried out. All the patients were treated using CRB Curvilinear approach. Patient follow up was recorded for 1 year on a regular interval basis. Symptoms of postoperative facial nerve injury were seen in 2 patients which recovered with time, postoperative complications were not encountered in any case and minimum scar mark hidden in the cervical skin crease. Hence open reduction and internal fixation for Subcondylar fracture of mandible by using the CRB modification of retromandibular approach is a good alternative for other conventional approaches in having ease of access, ease of fixation, reduced incidences of injury to facial nerve and its branches with good aesthetic outcome.
Keywords: Subcondylar fracture; CRB modification of retromandibular approach; Retromandibular approach; Aesthetic outcome